2008
DOI: 10.1523/jneurosci.3976-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Cold Spots: TRPM8-Expressing Sensory Neurons and Their Projections

Abstract: ) had drastically reduced cold responses and no menthol responses. In vivo, EGFPf-positive neurons marked a unique population of DRG neurons, a majority of which do not coexpress nociceptive markers. The fraction of DRG neurons expressing EGFPf was not altered under an inflammatory condition, although an increase in TRPV1-coexpressing neurons was observed. TRPM8EGFPf neurons project to the superficial layer I of the spinal cord, making distinct contacts when compared with peptidergic projections. At the periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
290
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(340 citation statements)
references
References 45 publications
40
290
0
Order By: Relevance
“…Whether TRPM8-mediated analgesia is dependent on peripheral and/or central sites of action is unknown but may be addressed now that TRPM8-expressing neurons and their peripheral and central fibers can be visualized by GFP expression driven by the TRPM8 promoter (76,77). Importantly, studies in humans and mice reveal species differences in pathways sensing innocuous cold: A-fiber block completely suppresses the cold response in humans (78), yet the majority of TRPM8-expressing fibers responsible for innocuous cold transduction in mice have small diameters (76,77) Noxious cold stimuli activate NSC currents and calcium influx (10,79) and decrease K + channel activity (80) and Na + /K + -ATPase function (65) ( Table 3). The temporal dissociation of the qualities of pain/ache vs. prickle/heat to noxious cold (3°C) suggest underlying differences in transduction mechanisms or information processing (66).…”
Section: Transduction Of Noxious Coldmentioning
confidence: 99%
“…Whether TRPM8-mediated analgesia is dependent on peripheral and/or central sites of action is unknown but may be addressed now that TRPM8-expressing neurons and their peripheral and central fibers can be visualized by GFP expression driven by the TRPM8 promoter (76,77). Importantly, studies in humans and mice reveal species differences in pathways sensing innocuous cold: A-fiber block completely suppresses the cold response in humans (78), yet the majority of TRPM8-expressing fibers responsible for innocuous cold transduction in mice have small diameters (76,77) Noxious cold stimuli activate NSC currents and calcium influx (10,79) and decrease K + channel activity (80) and Na + /K + -ATPase function (65) ( Table 3). The temporal dissociation of the qualities of pain/ache vs. prickle/heat to noxious cold (3°C) suggest underlying differences in transduction mechanisms or information processing (66).…”
Section: Transduction Of Noxious Coldmentioning
confidence: 99%
“…Using mammalian (i.e. mouse) (3,85,183,213) and non-mammalian (i.e. drosophila) (114,298) animal models, these investigations have significantly contributed to our understanding of how temperature is gated at a molecular level.…”
Section: Neurophysiology Of Temperature Sensationmentioning
confidence: 99%
“…Despite in the past 13 years consistent evidence has been provided for the importance of TRPM8 as molecular mediator of cold sensations in a number of mammalian (209,210) and nonmammalian (114) animal models, it is not until recently that the expression of this channel on those specific first order thermo-sensory afferents, which have been repeatedly shown to respond to skin cooling and to convey temperature-dependent sensory inputs within the spino-thalamocortical tract in mammals, has been thoroughly characterized (85). Dhaka et al (85) have shown that in mice, TRPM8 appears to be expressed on a specific population of first order neurons, whose body are located in the dorsal root ganglion, and whose projections terminate in the skin at the level of the stratum spinosum and granulosum (i.e.…”
Section: Non-noxious Cold Transductionmentioning
confidence: 99%
“…TRPV1 expressed in C-fibers is activated by heat (Ͼ43°C) (Caterina et al, 1997), and TRPV1-null mice are defective in sensing noxious heat (Caterina et al, 2000). TRPM8, which senses cold temperatures (Ͻ27°C) (McKemy et al, 2002;Peier et al, 2002), is expressed in nociceptive and nonnociceptive neurons and its loss causes deficiencies in cold sensation (Bautista et al, 2007;Colburn et al, 2007;Dhaka et al, 2007Dhaka et al, , 2008Takashima et al, 2007). TRPA1 is expressed in C-fibers, mostly accompanying TRPV1 , and acts as a sensor for harmful stimuli, although its responsiveness to noxious cold is controversial (Jordt et al, 2004;Bautista et al, 2006;Kwan et al, 2006;Sawada et al, 2007).…”
Section: Introductionmentioning
confidence: 99%